Identification of Career Choice for Vocational High School Students: A Review - Kurnia, Kurnia; Hakim, Dadang Lukman (JIPTEK: Jurnal Ilmiah Pendidikan Teknik dan Kejuruan, 2023)
Career uncertainty and unpreparedness of Vocational High School students in the face of the world of work are often associated with career choice factors (career choice). This causes many students who are not confident in choosing available job opportunities and some even choose not to work or become unemployed. This study aims to identify the factors that influence students' career decisions. This study applied the systematic literature review methodology to articles published in foreign journals. The researchers applied predetermined search parameters to locate ten pertinent articles published between 2019 and 2021. The study concluded that it is essential to recognize the factors that influence career decisions. It is crucial to assist students in concentrating more on the job search process and obtaining their desired positions. Employability, as determined by personal traits such as a proactive personality, self-reported education, personal preferences, performance expectations, days worked, industry experience, and years of study, was the most significant factor, followed by social status and prior work experience. This research also has educational and professional applications. Advisors who develop the personal potential of graduates can assist students and job seekers in adopting and exploring career strategies.